18F-Fluorodeoxyglucose and 11C-methionine positron emission tomography in relation to methyl-guanine methyltransferase promoter methylation in high-grade gliomas. Issue 3 (March 2015) - Choi, Hongyoon; Bang, Ji-In; Cheon, Gi Jeong; Kim, Yong Hwy; Park, Chul-Kee; Park, Sung-Hye; Kang, Keon Wook; Chung, June-Key; Kim, Euishin E.; Lee, Dong Soo
<x xml:space="preserve">Abstract</x> Introduction Methylation status of the methyl-guanine methyltransferase (MGMT) promoter is associated with a favorable response to a DNA alkylating agent in high-grade gliomas. We analyzed PET scans of patients with high-grade gliomas to determine whether the MGMT methylation status affects the tumor metabolic characteristics. Patients and methods Twenty-three patients with high-grade glioma, who were initially examined with 11C-methionine (MET) and 18F-fluorodeoxyglucose (FDG) PET, were retrospectively enrolled. MET and FDG PET images were coregistered to each other and quantitative uptake of MET or FDG was assessed using tumor-to-normal uptake ratio of the cortex (TNR). TNRs for MET and FDG PET were compared between the two groups classified by MGMT promoter methylation status. Results Maximum TNRFDG of the MGMT methylated group was significantly higher than that of the MGMT unmethylated group (1.80±0.90 vs. 1.29±0.19; P=0.02). The MGMT methylated group also showed a trend for increased mean TNRFDG compared with the unmethylated group (0.85±0.21 vs. 0.72±0.11; P=0.10). There was no significant difference in TNRMET between the groups. In subgroup analyses with WHO grade 3 and 4, a trend for higher maximum TNRFDG was found in the MGMT methylated group compared with the unmethylated group. Conclusion The MGMT methylated group showed higher glucose metabolism compared with the unmethylated group, whereas MET uptake did not show a significant difference. This suggests that MGMT methylation in high-grade gliomas could affect the tumor glucose metabolism. Thus, MGMT methylation status can cause a discrepancy in the prognostic prediction of high-grade gliomas by FDG PET, especially in patients scheduled for DNA alkylating chemotherapeutics.